Implementation of Merdeka Curriculum Development for Islamic Religious Education: A Case Study in a Junior High School - Wijayanti, Nur Hanifah; Hamami, Tasman (research, training and philanthropy institution Natural Aceh, 2024)
This research discusses the implementation of the Islamic Religious Education curriculum reform that is currently being carried out, taking into account the